The Effect of Customer Relationship Marketing and Trust on Customer Loyalty (Case Study on Jne Nusa Indah Customers Bengkulu City) - Dea Ananda Regita; Ade Tiara Yulinda (UNIVED Press, 2024)
This study aims to determine the effect of customer relationship marketing and trust on customer loyalty (case study on JNE Nusa Indah customers in Bengkulu City). This type of research uses quantitative descriptive research methods. The population in this study is customers of JNE Bengkulu City with a total of 110 respondents. The data collection method uses questionnaires and uses analytical techniques using multiple linear regression analysis tests and hypothesis tests, namely t tests and f tests. Based on the results of multiple linear regression, the form of the regression equation Y = 15.287 + 0.201 (X1) + 0.190 (X2) and the results of the t test and f test of this study can be concluded that customer relationship marketing has a significant effect on customer loyalty, this is evidenced by the results of the t test showing the value of thit>ttable (2.066> 2.002) and (sig a = 0.03 < 0.050). This means H_0 is rejected and H_a is accepted. Trust has a significant effect on customer loyalty, this is evidenced by the results of the t test showing the value of t_hit>t_table (2.055 > 2.002) and (sig α = 0.02 F_table, namely (50.277 > 2.69) and (sig α = 0.000 < 0.050). This means H_0 is rejected and H_a is accepted.